2021
DOI: 10.1002/adma.202102900
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Photoclick (Bio)Resins for Fast Volumetric Bioprinting

Abstract: Volumetric printing (VP) is a light‐mediated technique enabling printing of complex, low‐defect 3D objects within seconds, overcoming major drawbacks of layer‐by‐layer additive manufacturing. An optimized photoresin is presented for VP in the presence of cells (volumetric bioprinting) based on fast thiol–ene step‐growth photoclick crosslinking. Gelatin‐norbornene (Gel‐NB) photoresin shows superior performance, both in physicochemical and biocompatibility aspects, compared to (meth‐)acryloyl resins. The extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(125 citation statements)
references
References 66 publications
1
124
0
Order By: Relevance
“…This specific size was selected to generate filaments that could completely embed the produced organoids, even though finer printing resolution are possible as shown before in Figure 1B,C, in which resolution superior to what is shown with volumetric printing up to date has been demonstrated. [15,16,24,25] In an ideal print, both the thick border of the disc and the thinner filament, herein used as a benchmark to quantify the printing resolution, should solidify at the same time after receiving the same, optimal light dose. Exceeding this optimal dose will cause overcuring of the fine feature, thickening of the filament wall, and eventually clogging of the disc.…”
Section: Resultsmentioning
confidence: 99%
“…This specific size was selected to generate filaments that could completely embed the produced organoids, even though finer printing resolution are possible as shown before in Figure 1B,C, in which resolution superior to what is shown with volumetric printing up to date has been demonstrated. [15,16,24,25] In an ideal print, both the thick border of the disc and the thinner filament, herein used as a benchmark to quantify the printing resolution, should solidify at the same time after receiving the same, optimal light dose. Exceeding this optimal dose will cause overcuring of the fine feature, thickening of the filament wall, and eventually clogging of the disc.…”
Section: Resultsmentioning
confidence: 99%
“…For example, biphasic calcium phosphate (BCP) and matrigel/alginate hydrogel composites were synthesized by EBB to induce osteogenesis of incorporated MSCs as an osteoinductive bone filler at the area of bone defects ( Fedorovich et al, 2011 ). In addition, volumetric 3D bioprinting is a light-mediated technique, which enables excellent cell viability, structural fidelity, and tissue maturation potential ( Rizzo et al, 2021 ). It has been reported that volumetric tomographic bioprinting of a bone model could promote osteocytic differentiation, which would be a powerful tool for biofabrication of 3D bone-like tissues ( Gehlen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there was a need for postprinting processing when GelMA was used as the bioresin for volumetric tomographic printing, where the printed constructs were further immersed into a secondary photoinitiator bath, followed by additional photoirradiation. By contrast, a recent publication by Rizzo et al [200] showed that when gelatin-norbornene (GelNB) was used for volumetric tomographic printing, there was no need for postprinting crosslinking. Although both GelMA and Reproduced with permission.…”
Section: Natural-based Bioresinmentioning
confidence: 97%